Development of a website-based blended learning model to optimize vocational skills learning at MAN Alor - Hadi Abdul Aziz Kammis; Budi Santosa; Edhy Susatya; Heru Raharjo (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2026)
Limited classroom availability at Madrasah Aliyah Negeri (MAN) Alor requires the vocational skills program to be conducted in two shifts, reducing instructional time from 45 minutes to 25 minutes per lesson hour. This condition calls for a flexible learning model so that theoretical reinforcement, practical demonstrations, assignments, and evaluation do not rely solely on face-to-face meetings. This study aimed to analyze the existing vocational skills learning model, develop a subject-based website-supported blended learning model, and examine the feasibility of the developed model. The study employed a research and development method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects included vocational skills teachers, students, media experts, material experts, and learning practitioners. Data were collected through observation, interviews, documentation, expert validation, practitioner validation, and student response questionnaires. The data were analyzed using qualitative and quantitative descriptive techniques with feasibility percentages. The findings showed that the subject-based website-supported blended learning model was categorized as highly feasible, with media expert validation at 89%, material expert validation at 91%, practitioner validation at 88.5%, and student responses at 88.4%. These findings indicate that the developed model is feasible as an alternative strategy for expanding learning access and supporting vocational skills learning in madrasahs with limited educational facilities.